THE RELATIONSHIP BETWEEN (ORIGIN, SCIENTIFIC PART AND LANGUAGE OF STUDY) AND USING EMOJIS BETWEEN THE STUDENTS OF THE UNIVERSITY OF ZAKHO - Salih, Salwa; Kamel, Warhel (Humanities Journal of University of Zakho, 2025)
Emojis are the symbols that join writing symbols in social media. And they are also a part from what a message of someone carries. Someone who message others tends to use them for expressing a case or expressing an excitement or for abbreviating words, to write a little speech and also they use them for decorating the appearance of the speech, influence and avoiding mystery on the message. This study has been done under the title “ the relationship between (origin, scientific part and language of study) and using emojis between the students of the university of Zakho”. It seeks to answer this main question: do (origin, scientific part and study of language) variables have a relationship with the type of emojis? The study has been done in a questioning manner with 120 students from the university of Zakho of origin, scientific part and study of language differently and the data has been explained by SPSS program. The main hypothesis of the study is that the mentioned variables have relationship with choosing the type of emojis. After taking data’s and explaining them it was clear that origin and scientific part have relationship with choosing the type of emojis, but language of study doesn’t have any relationship with it.